Feeling Deficient but Reluctant to Improve: How Perceived Control Affects Consumers' Willingness to Purchase Self-Improvement Products Under Self-Deficit Situations - Song, Wei; Jin, Xiaotong; Gao, Jian; Zhao, Taiyang (Frontiers in Psychology, 2021)
This study explored how perceived control affects consumers’ willingness to purchase self-improvement products under self-deficit situations. For this purpose, three experiments were conducted to examine the following sources of control: the controllability of self-deficits (Experiment 1); the locus of control (Experiment 2); and situational perceived control (Experiment 3). According to the results, higher perceived control can reduce consumers’ defensive reaction tendencies, thus increasing their willingness to purchase products that claim to improve their current deficits. Moreover, the aforementioned effect only occurs in within-domain improvement products, rather than without-domain improvement products.